Perinatal Exposure to Environmental Pollutants and Infant Immune System Development Mechanisms - Rehman H, Dr. Ubaidur; G, Dr. Anbazhagan; S, Uma; Kumar A, Mr. Anish (Adolescência e Saúde, 2026)
Background: Exposure to environmental pollutants during the perinatal period has emerged as a major public health concern due to its potential impact on the development of the infant immune system. Exposure in utero and during early life to air pollutants, heavy metals, pesticides, endocrine-disrupting chemicals and industrial contaminants may interfere with immune maturation and increase susceptibility to infections, allergies and immune-related disorders. Objective: The aim of this study was to investigate the mechanisms of perinatal exposure to environmental pollutants on the development of infant immune system and evaluate health outcomes. Methodology: We conducted a systematic review of recent epidemiological and experimental studies published between 2018 and 2025. Relevant studies on prenatal and neonatal exposure to environmental pollutants and their effects on immune biomarkers, inflammatory responses and immune regulation were reviewed. Findings: The evidence reviewed suggests that perinatal pollutant exposure was associated with a 15–35% increase in inflammatory biomarkers, a 20–30% decrease in immune regulatory function and a 25% increased risk of allergic and respiratory disorders in infancy. Pollutants influenced the immune system by affecting immune cell differentiation, altering cytokine production, inducing oxidative stress and causing epigenetic modifications that affected the development of the immune system. Conclusion: Environmental pollutants exposure in the perinatal period can negatively impact the immune development of infants through multiple biological pathways. Promoting healthy immune maturation and preventing immune-related diseases in the long term is vital to minimize maternal and neonatal exposure to environmental contaminants.